PENGARUH FAKTOR MAKROEKONOMI TERHADAP PENINGKATAN KINERJA ASURANSI SYARIAH DI INDONESIA - Sari, Windi Prastika; Pertiwi, Ruspita Rani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the influence of macroeconomic factors on improving the performance of sharia insurance in Indonesia in the period 2015-2022. The methodology used is a quantitative approach with panel data analysis, involving independent variables such as Gross Domestic Product (GDP), inflation, interest rates, unemployment rates, and exchange rates, as well as dependent variables in the form of sharia insurance performance measured by total asset indicators. The study uses a panel data regression model, including Pooled Ordinary Least Squares (POLS), Fixed Effects Model (FEM), and Random Effects Model (REM), with statistical tests such as the Chow Test, Hausman Test, and LM Test to determine the best model. The results of the study show that GDP and exchange rates have a significant positive effect on sharia insurance performance, while inflation and unemployment rates have a negative impact. Interest rates do not show a significant effect, reflecting people's preferences for sharia-based products that are more influenced by spiritual awareness than interest rate conditions. This study emphasizes the importance of macroeconomic stability and transparent management of sharia funds to support the development of the sharia insurance industry in Indonesia.. Keyword: sharia insurance;panel data;macroeconomic factors. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh faktor-faktor makroekonomi terhadap peningkatan kinerja asuransi syariah di Indonesia pada periode 2015-2022. Metodologi yang digunakan adalah pendekatan kuantitatif dengan analisis data panel, melibatkan variabel independen seperti Produk Domestik Bruto (PDB), inflasi, suku bunga, tingkat pengangguran, dan nilai tukar, serta variabel dependen berupa kinerja asuransi syariah yang diukur melalui indikator total aset. Penelitian menggunakan model regresi data panel, meliputi Pooled Ordinary Least Squares (POLS), Fixed Effects Model (FEM), dan Random Effects Model (REM), dengan uji statistik seperti Uji Chow, Uji Hausman, dan Uji LM untuk menentukan model terbaik. Hasil penelitian menunjukkan bahwa PDB dan nilai tukar memiliki pengaruh positif signifikan terhadap kinerja asuransi syariah, sementara inflasi dan tingkat pengangguran berdampak negatif. Suku bunga tidak menunjukkan pengaruh signifikan, mencerminkan preferensi masyarakat terhadap produk berbasis syariah yang lebih dipengaruhi oleh kesadaran spiritual dibandingkan kondisi suku bunga. Penelitian ini menegaskan pentingnya stabilitas makroekonomi dan pengelolaan dana syariah yang transparan untuk mendukung perkembangan industri asuransi syariah di Indonesia. Kata kunci: asuransi syariah;data panel;faktor makroekonomi.